The Impact of Covid-19 on Islamic Economics & Finance Industry: A Bibliometric Analysis - Evania; Aam (Journal of Islamic Economics Literatures, 2021)
Since Covid 19 appeared at the end of 2019, this virus has caused fundamental changes in consumer behavior, economy, and industries worldwide, including halal and Islamic finance. This study aims to analyze literature studies and find out the research development related to the impact of Covid-19 on the Islamic economics and finance industry in the world by reviewing 62 documents from 2020-2021 on the Scopus database. VoS viewer to find out the bibliometric map of research development related to the impact of Covid-19 on the Islamic economics and finance industry. The results show an increase in the number of papers published on this theme in recent years from 2020 to 2021. Furthermore, based on the results from reviewing several studies, it was found that the Covid-19 pandemic impacted Islamic Economics and Finance. Industry. Since Covid 19 appeared at the end of 2019, this virus has caused fundamental changes in consumer behavior, economy, and enterprises worldwide, including halal and Islamic finance.